Diuresis Activity of A Combination of Alang-Alang Rhyme Extract (Imperata cylindrical L.) and Cat's Whistle Leaves (Orthosiphon stamineus L.) in Male Mice (Mus musculus). - Edi Kamal, Sainal; Yusti, Yusti (Politeknik Sandi Karsa, 2022)
Diuretics are substances that can increase the rate of excretion of urine volume and indicate the amount of expenditure (loss) of solutes and water. The Alang-Alang rhizome and the Cat's Whiskers plant are one of the many plants that have many advantages and have been used for a long time in an effort to maintain health. This study aims to determine the combined activity of Alang-alang (Imperata cylindrical L.) Rhizome Extract and Kumis Leaf Extract. Cat (Orthosiphon stamineus L.) as a diuretic in mice (Mus musculus). The test animals were divided into 5 groups, each group consisted of 3 test animals. Group I was given a 1% w/v Na-CMC colloidal solution as a control. Groups II, III and IV were given a suspension of a combination of Alang-Alang rhizome extract and Kumis Kucing Leaf extract with each dose of 100 mg/Kg BW ratio (1 : 1), (1 : 2) and (2 : 1) as the treatment group. The highest to lowest diuretic activity sequentially with the average value being furosemide (3.67), combination (Alang-Alang rhizome: Daun Kumis Kucing) 2 : 1 (2.67), combination (Rimpang Alang-Alang: Daun Kumis Kucing) ) 1 : 2 (1,33), and a combination (Alang-Alang Rhizome: Cat's Whisker Leaf) 1 : 1 (1,33). The largest combination dose that gave an increase in urinary frequency was at a combination dose of 2: 1 (Rhimpang Alang-Alang: Daun Kumis Kucing) with an average value of 2.67.